OSRR-based BPF with Square Groundplane Window - Risma Safitri; Achmad Munir (IAES Indonesia Section, 2014)
In this paper, a bandpass filter (BPF) composedof open split-ring resonator (OSRR) structure with squaregroundplane windows underneath the structure is investigatednumerically and experimentally. Square groundplane windowsare proposed to enhance the property of OSRR-based BPF inovercoming the passband bandwidth response. The designed BPFis constructed of 3 cascaded OSRRs connected with microstriplines. Some parametrical study to obtain the optimum bandwidthresponse is carried out by changing the dimension of squaregroundplane window in the design process. The filter is thendeployed on a 0.8mm thick FR4 Epoxy dielectric substrate withthe dimension of 60mm in length and 20mm in width. Fromthe experimental characterization, the realized OSRR-based BPFwith the dimension of each square groundplane window of 12mm× 12mm shows the bandwidth response of 0.81GHz ranges from1.75GHz 2.56GHz which is comparable with the numerical one.